Can plain packaging be effective without a standard design? - AY, NADİYE PINAR (My University, 2021)
Objective: In Turkey plain packaging has been in practice since January 2020 based on the amendment to the Law on Prevention and Control of Hazards of Tobacco Products. However plain cigarette packages are presented in different shape and appearances in the market, without a uniform standard form. The aim of this study was to explore the perception of smokers regarding the different designs of packages appearing in the market. Methods: This was a qualitative study. The researchers obtained all the tobacco products in the market and formed a set which had identical pictorials, but had different pack shapes. Data were collected through in-depth interviews from a convenient sample of smokers. Participants were shown the set containing differently designed products and asked to evaluate each package. Interviews were audiotaped, transcribed verbatim and thematic content analysis was conducted. Results: Of the 11 participants, three were women. The age of the participants ranged between 29- 46 years. The standard pack was stated to have an unattractive design, and participants indicated that it was hard to carry in a purse and in the pocket due to its large size. The participants mostly preferred narrow and long designs with a flip lid. The women defined such packages as “stylish” and “pretty”. Long and narrow designs were also preferred because they were very convenient for carrying in the pocket for men and in the purse for women. Measurements and Main Results: Tobacco industry tries to prevent the impact of plain packaging through non-standard appealing pack designs. Plain packaging without being presented in a standard design will not have a deterrent effect on smoking.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Education; Smoking; Health policy